Outbreak of tuberculosis after minimal exposure to infection. Issue 6234 (19th July 1980) - Rao, V R; Joanes, R F; Kilbane, P; Galbraith, N S
Abstract : The identification of a case of respiratory tuberculosis in a swimming-baths attendant whose sputum was smear positive was followed by intensive contact tracing of children aged 8-11 years who had visited the baths. An outbreak was discovered that otherwise might not have been detected. Out of 3764 children, 108 (2.9%) had evidence of infection: there were 16 cases of tuberculosis, of which 11 were symptomless but showed lesions on chest radiography, and a further 92 with tine test grade 3 or 4 without clinical or radiological signs. The contact of these children with the index case was apparently minimal. Early detection, isolation, and treatment of infectious cases of respiratory tuberculosis and vigorous contact tracing should be given more priority in tuberculosis control.